FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN PELANGGAN CAFEMART MANDIRI SEJAHTERA DI SURAKARTA - Muhammad Adi Suseno; Ari Susanti (JURNAL WIRANOMIKA, 2025)
Abstract: Customer satisfaction is a key indicator of business success, particularly in the culinary sector where competition is highly intense. This study aims to examine the effect of product quality, price, and cleanliness on customer satisfaction at Cafemart Mandiri Sejahtera. The research employed a quantitative approach by distributing questionnaires to 97 respondents who were customers of Koperasi Mandiri Sejahtera. The collected data were analyzed using reliability and validity tests, classical assumption tests, multiple linear regression analysis, as well as F-tests and t-tests. The results show that all independent variables—product quality, price, and cleanliness—have a positive partial effect on customer satisfaction, with product quality emerging as the most dominant factor. These findings suggest that improving product quality and maintaining environmental cleanliness can enhance customer satisfaction and strengthen customer loyalty toward Cafemart.      Keywords: Product Quality, Price, Cleanliness, Customer Satisfaction